Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

use the elimination method to solve the system of equations. a+7b=7 a+2b=-3

I got my questions answered at in under 10 minutes. Go to now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

subtract the 2 equations, what u get ?
I am sorry don't understand
let me give you an example on how to subtract equations, let the 2 equation be say, 2x+3y =7 2x-3y =2 now if i subtract the 1st equation from 2nd equation, i get (2x-3y) - (2x+3y) = 2-7 so, 2x-2x-3y-3y=-5 0-6y=-5 so, y = 5/6 in same manner, you try for your question of a+7b=7 a+2b=-3

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

very close,but its 7b-2b = 7-(-3) can you proceed ?
7-2 = 5 7- (-3) = 7+3 =10 -_-
so b=5/10?
7b-2b = 7-(-3) 5b = 10 b=10/5 = 2 got this ?
still confused
on which step ?
7-(-3) since it has a minus sign in front i believed it was to be subtracted not added.
- * - = + so, 7 - (-3) became 7+3
ok now i understand
so the final answer would be 2
b=2 you still need to find 'a' put b=2 in any 1 of the original equation to get a
multiply the first equation by a -1. Doing this will cancel out the a's. You can then solve for b. Once you have solved b, substitute that in for b in either of the original equations and you will solve a. You can then check your answer by subbing in known variables in either of the original equations and if they equal, your answers are correct :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question